Gross and net erosion balance of plasma-facing materials in full-W tokamaks. (23rd September 2021) - Hakola, A.; Likonen, J.; Lahtinen, A.; Vuoriheimo, T.; Groth, M.; Kumpulainen, H.; Balden, M.; Krieger, K.; Mayer, M.; Schwarz-Selinger, T.; Brezinsek, S.; Kelemen, M.; et al.
Abstract: Gross and net erosion of tungsten (W) and other plasma-facing materials in the divertor region have been investigated in deuterium (D) and helium (He) plasmas during dedicated experiments in L- and H-mode on ASDEX Upgrade and after full-length experimental campaigns on the WEST tokamak. Net erosion was determined via post-exposure analyses of plasma-exposed samples and full-size wall components, and we conclude that the same approach is applicable to gross erosion if marker structures with sub-millimeter dimensions are used to eliminate the contribution of prompt re-deposition. In H-mode plasmas, gross erosion during ELMs may exceed the situation in inter-ELM conditions by 1–2 orders of magnitude while net erosion is typically higher by a factor of 2–3. The largest impact on net erosion is attributed to the electron temperature while the role of the impurity mixtures is weaker, even though both on ASDEX Upgrade and WEST significant amounts of impurities are present in the edge plasmas. Impurities, on the other hand, will lead to the formation of thick co-deposited layers. We have also noted that with increasing surface roughness, net erosion is strongly suppressed and the growth of co-deposited layers is enhanced. In He plasmas, gross erosion is increased compared to D due to the higher mass and charge states of the plasma particles, resulting from larger energies due to sheath acceleration, but strong impurity fluxes can result in apparent net deposition in the divertor. Our results from ASDEX Upgrade and WEST are comparable and indicate typical net-erosion rates of 0.1–0.4 nm s −1, excluding the immediate vicinity of the strike-point regions.